Desempeño de un almidón natural obtenido de las cascaras de plátano en el control de propiedades de reología, lubricidad y filtrado de un fluido de perforación polimérico a nivel de laboratorio. (2021)
Polymeric drilling fluids are one of the most used in the oil industry, however, the additives used for this mud such as PAC-L and PAC-R raise the cost of formulation. This project aims to evaluate the performance of banana starch in controlling the rheology, lubricity and filtering properties of a water-based polymeric drilling fluid at the laboratory level. To achieve the fulfillment of the general objective, starch was made from the synthesis of banana peel, a drilling fluid was designed that was used as a comparative basis, and 10 drilling fluids were prepared in which starch was used. banana as a substituent for the additive’s PAC-L and PAC-R. Rheology, lubricity and filtering tests were run on all the fluids produced and from this the optimal concentration of starch that should be used to obtain a drilling fluid similar to the base mud of the study was determined.